Efficacy and safety analysis of neoadjuvant chemotherapy combined with immunotherapy in patients with muscle-invasive bladder cancer - Yu, Yanhang; Zhang, Chuanao; Chen, Hao; Zhang, Jianglei; Ouyang, Jun (Frontiers in Immunology, 2024)
IntroductionThis study examined the efficacy and safety of neoadjuvant chemotherapy combined with immunotherapy in patients with muscle-invasive bladder cancer (MIBC).MethodsThis retrospective cohort study included patients diagnosed with MIBC at the First Affiliated Hospital of Soochow University between January 1, 2020, and December 31, 2023, assigned to either chemotherapy (gemcitabine with cisplatin) or combination (chemotherapy plus toripalimab or tislelizumab) groups based on the neoadjuvant treatment regimen. Key metrics, including pathological downstaging rate (PDR), pathological complete response rate (PCRR), and incidence and severity of adverse events (AEs), were compared between groups.ResultsThis study included 53 patients (mean age: 67.21 years). In the combination group, 14 patients (51.85%) achieved pathological complete remission (ypT0), and seven (25.93%) achieved partial remission (ypT1), resulting in a PDR and PCRR of 77.78 and 51.85%, respectively. In the chemotherapy group, six patients (23.08%) achieved complete remission, and five (19.23%) achieved partial remission, resulting in a PDR and PCRR of 42.31 and 23.08%, respectively. Differences between groups were statistically significant (p < 0.05). There were no significant differences in pathological downstaging or complete remission rates among subgroups in the combination group (p > 0.05). No serious allergic reactions or fatal AEs were detected in either group, with no grade 4 AEs. Grade 3 AE rates were 22.22 and 20.83% in the combination and chemotherapy groups, respectively, although non-significant (p > 0.05).ConclusionNeoadjuvant chemotherapy combined with immunotherapy had enhanced efficacy and manageable safety in patients with MIBC, suggesting its potential for integration into clinical practice.